Brydes do divers / Harzeedly Micky Lusiwoi... [et al.] - Lusiwoi, Harzeedly Micky; Jamil, Mohd Izwan; Julkipli, Rosnani; Sidik, Noraidah; Ismail, Mohammad Iszwan (Faculty of Administrative Science and Policy Studies, 2007)
BRYDE'S DO DIVERS partnership business was planned by 5 students at the beginning of semester through Fundamental of Entrepreneurship (ETR300) course. The main purposes of our business are to produce commercial scuba services in Sabah. We involve in this business because this is one of the important attraction sources and of course the potential of this business will develop well in addition. People will always demand for scuba services. We produce services for local people and foreign from other country. In the first and second year, we will concentrate around the Tunku Abdul Rahman Marine Park area and after that we will expand our business. Tunku Abdul Rahman Marine Park is a famous and suitable place for scuba diving and that is the reason why we choose the place for our business. With this business, we hope that customers will satisfy with our scuba services and we will make sure they will get good and better services.